ANALISIS PEMANFAATAN ARTIFICIAL INTELLIGENCE SEBAGAI MEDIA PEMBELAJARAN OLEH GURU SEKOLAH DASAR NEGERI 02/III SUNGAI TUTUNG - Diva Apri Mulya; Muhammad Ali Imron; Egi Agustandi; Shobrina Fitri; Ria Roaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of Artificial Intelligence (AI) has created new opportunities to enhance the quality of learning in elementary schools. This study aims to analyze the use of AI as a learning tool by teachers at SD Negeri 02/III Sungai Tutung. A qualitative, descriptive research approach was employed. Research informants included the school principal and teachers, selected using purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data validity was ensured through source and technique triangulation, while data analysis utilized the interactive model proposed by Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The results indicate that teachers have utilized various AI applications—such as ChatGPT, Google Gemini, and Canva AI—to compile teaching modules, develop learning materials, create assessment instruments, and source learning content. The use of AI offers benefits such as time efficiency, enhanced teacher creativity, and the presentation of more engaging learning materials, thereby supporting a more innovative learning process. However, the use of AI faces several challenges, including varying levels of teacher digital literacy, limited internet access, and the need to verify AI-generated information. Therefore, the use of AI requires support through improved teacher digital competence, adequate technological infrastructure, and the application of ethical principles to ensure it optimally enhances the quality of learning in elementary schools.